Experimental research of the vapor zone between two coalescing droplets of heated water. (July 2021) - Kuznetsov, G.V.; Piskunov, M.V.; Shlegel, N.E.; Strizhak, P.A.
Abstract: Droplet interaction regimes in a gas depend on collision parameters and liquid properties. Such interactions may occur at various droplet and gas temperatures. A significant impact on droplet interaction may come from vaporization. It has been largely overlooked as a factor of switching between collision regimes (coalescence, bounce, separation, and disruption) and outcomes. We present the experimental research into the collision characteristics of water droplets heated up to the boiling temperature in a gas medium. The experiments are conducted with the main droplet parameters varied in the following ranges: 0.1–5 m/s velocities, 0.1–1 mm dimensions, and 0–90° impact angle. The videos of colliding heated droplets illustrate the formation of the interface within the coalesced droplet. A vapor zone is identified that is formed due to intense water evaporation from the surface of the two contacting droplets. The colliding droplets are found to localize a certain volume of vapor when the resulting interaction velocities are low and the collisions are head-on. The main characteristics of such vapor zones are established. The most valuable experimental findings are the vapor zone characteristics versus the Weber number, relative interaction velocity, and droplet size ratio, as well as the joint impact of the said factors. Graphical abstract: Unlabelled Image Highlights: Vapor zone is formed near the interface of the colliding heating water droplets. Maximum thickness of vapor zone reached 12–18% of the agglomerated droplet diameter. Vapor zone lifetime at the Weber number of 0.1–18 ranged from 2·10 −3 s to 20·10 −3 s. This lifetime at the interaction parameter of 0–1 ranged from 2·10 −3 s to 15·10 −3 s. Ratio of vapor zone lifetime to the droplet coalescence time varied from 0.1 to 0.8.